Analisis Perilaku Merokok Pada Remaja di Dusun Jaya Sakti Desa Kuala Mandor B - Jamil, Nurul; Hidayah, Nurul (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Smoking behavior is still an unresolved problem today. This is indicated by the high percentage of smokers in Indonesia. The problem of smoking behavior also occurs in school adolescents. The percentage of school-age adolescent smokers in Indonesia is 9-10% of the total adolescents. This figure is still quite high. The most critical period to initiate smoking among male adolescents in Indonesia is in mid-adolescence or at the age of middle school children. At this time adolescents experience many kinds of changes in themselves, namely physical and psychological changes, both individually and in social roles in the family, school, and society. Many factors influence adolescent smoking behavior. This study aims to obtain an overview of smoking behavior in adolescents in Kuala Mandor Village B. This study will use quantitative research methods with a cross sectional approach. Sampling will be done with purposive sampling technique with a minimum population of 30 adolescents. Smoking behavior in adolescents in Jaya Sakti Hamlet, Kuala Mandor B District shows that almost half of the respondents (46%) have smoking behavior in the category of heavy smokers. With the characteristics of respondents, almost all respondents (93%) were aged 15-25 years, most of the respondents (68%) were unmarried, and most of the respondents (67%) had a high school education. Then almost half of the respondents (41%) said the reason for smoking was because of the influence of friends. It can be concluded that smoking behavior in adolescents in Jaya Sakti Hamlet, Kuala Mandor B Subdistrict, is in the category of heavy smokers.  Keywords: Smoke, Behavior, Adolesence, Health  ABSTRAK Perilaku merokok masih menjadi masalah yang belum teratasi sampai saat ini. Hal ini ditunjukkan oleh masih tingginya persentase perokok di Indonesia. Masalah perilaku meorkok juga terjadi pada remaja sekolah. Persentase perokok usia remaja sekolah di Indonesia 9-10% dari total remaja. Angka ini masih cukup tinggi. Periode yang paling kritis untuk berinisiasi merokok dikalangan remaja laki-laki di Indonesia adalah di pertengahan masa remaja atau pada usia anak sekolah menengah. Pada masa ini remaja banyak mengalami berbagai macam perubahan pada dirinya, yaitu perubahan fisik maupun psikis, baik secara individual maupun dalam  peranan  sosial  dikeluarga,  sekolah,  dan  masyarakat. Penelitian ini bertujuan untuk mendapatkan gambaran perilaku merokok  pada remaja di Desa Kuala Mandor B. Penelitian ini akan menggunakan metode penelitian kuantitatif dengan pendekatan cross sectional. Pengambilan sampel akan dilakukan dengan tekknik purposive sampling. Perilaku merokok pada remaja di Dusun Jaya Sakti Kecamatan Kuala Mandor B menunjukkan bahwa hampir setengahnya dari responden (46%) memiliki perilaku merokok kategori perokok berat. Dengan karakteristik responden hampir seluruhnya responden (93%) berusia 15-25 tahun, sebagian besar dari responden (68%) berstatus belum menikah, serta sebagian besar dari responden (67%) berpendidikan SMA. Kemudian hampir setengahnya dari responden (41%) mengatakan alasan merokok karena pengaruh teman. Dapat disimpulkan bahwa perilaku merokok pada remaja di Dusun Jaya Sakti Kecamatan Kuala Mandor B kategori perokok berat. Kata Kunci: Kesehatan, Perilaku, Remaja, Merokok